TANNINS IN GOAT DIETS MODIFY MANURE TURNOVER IN A SUBTROPICAL SOIL. (24th July 2017) - INGOLD, MARIKO; SCHMIDT, SASKIA; DIETZ, HERBERT; JOERGENSEN, RAINER GEORG; SCHLECHT, EVA; BUERKERT, ANDREAS
SUMMARY: Quality of animal manure as a nutrient source for crops and as a soil conditioner depends on how fast the organic matter is decomposed, releasing plant nutrients or building up the soil organic matter (SOM) pool. This turnover process is governed by manure composition, soil temperature, soil moisture and secondary metabolites in the manure such as tannins. To investigate the turnover and nutrient release from tannin-containing manure, a litterbag experiment was conducted in an irrigated lowland soil of northern Oman. A standardized quebracho tannin extract (QT) was either added to the goats' diet and defecated with manure (QTf), or added to manure in a QT water suspension (QTc) prior to field application. Litterbags were installed within a two-year field experiment at 10-cm depth at the beginning of a consecutive sweet corn and radish cultivation, followed by their recovery every 2-–6 weeks until crop harvests. The litterbags contained pure goat manure (control) and the two types of QT-amended goat manure. Generally, QT increased OM remaining in litterbags at sampling by up to 22% compared with the control. QT reduced relative C, N, P and K release by 10% to 63% compared with the control, but effects were contradictory under sweet corn and radish. While under radish, both QT treatments reduced or tended to reduce C, N, P and K release from manure, QTc even increased N and P release under sweet corn. QTf, on the other hand, did not affect C, P and K release under sweet corn, whereas N release was reduced by 36–63% under both crops. As quebracho tannins in goat manure slowed down organic matter decomposition and reduced nutrient release, they may be useful agents in manure application to increase SOM pools and soil nutrient pools. However, the immobilization particularly of N by tannins can reduce the availability of this nutrient to crops.